L’esthétique au prisme de la trans‑caribéanité : Perspectives décoloniales sur l’art jamaïcain et martiniquais - Frédéric Lefrançois (Transatlantica)
Could New World Art constitute the locus of the transfer between antagonistic libidinal, poly-traumatic economies? If the artist born in the Americas cannot overlook the weight of the slave trade, of slavery and colonization, in virtue of their quality as founding traumas, then the fragmentation induced by all their breaking-lines represents a real aesthetic and political challenge. Consequently, two opposite paths can be envisaged: to opt for unconscious scarring by way of oblivion, or to accept traumatic memory so as to aestheticize resistance against cultural genocide. In the French and English-speaking Caribbean, this dilemma has tormented the aesthetic consciousness of three successive generations of artists inheriting a traumatic bequeathal, like the Jewish artists-legatees of the Shoah. What should be done with this inheritance? Should one engage oneself on the path of oblivion, or even negation, and thus follow the example of amnesia proselytes, under the pretext of “progress”? Or should one assume fully the burden of this heritage and transmute it into a principle of aesthetic creation helping to preserve cultural memories and identities? It is a contention of this essay to answer this question by correlating the evolution of two Caribbean artistic movements with similar aspirations: the Atelier 45, born in Martinique, and the Jamaican Art Movement which appeared in Jamaica.